GUIDANCE AND COUNSELING PROGRAM PREPARATION - Bakhrudin All Habsy; Ayu Anggraini; Shaleha, Aula Niswa; Zainiah, Nisrina Salwa; Zahroh, Ummu (PT Altin Riset Publishing, 2025)
Guidance and counseling teachers have an important role in achieving optimal learner development. Thus, the need for a good understanding of the preparation of the counseling program is very important. Guidance and counseling programming is the process of planning programs to help students develop the abilities and skills needed to achieve their life goals in a structured and systematic manner. The purpose of this study is to explain the aspects in the process of preparing the counseling program in order to maximize the performance of counseling teachers optimally and sustainably. This research uses a literature study or literature review by reviewing the latest and relevant scientific books and journals as a source of literature. The results of the research on the preparation of the counseling program include: (1) Definition of the counseling program, (2) The role of the counseling teacher in the preparation of the counseling program, (3) The objectives and benefits of the preparation of the counseling program, (4) The components of the counseling program services, (5) The stages of preparing the counseling program, (6) Needs assessment, (7) Needs analysis, and (8) Independent curriculum-based counseling programs. Through the implementation of the guidance and counseling program preparation that has been well structured in accordance with the provisions and needs, it will have a significant positive impact on all students, especially the smooth implementation of the guidance and counseling program itself.